2023
DOI: 10.3389/fcvm.2023.1037227
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of arterial elastic function in middle-aged and elderly people: A population-based cross-sectional study from a low-income population in China

Abstract: BackgroundArterial stiffness is closely associated with the occurrence of many cardiovascular and cerebrovascular diseases. However, the risk factors and mechanisms related to arterial stiffness development have only been partially elucidated. We aimed to describe arterial elastic function and its influencing factors in middle-aged and elderly people in rural China.MethodsThis was a cross-sectional study conducted among residents, aged ≥45 years, of Tianjin, China, between April and July 2015. Data regarding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Several risk factors have been identified and, among these, increased arterial stiffness has gained attention due to its correlation with many cardiovascular endpoints [ 1 ]. Studies reported the determinants of arterial stiffness [ 2 ], which contributes to the stiffening of the wall artery. The structure of the vessel wall varies along the vascular tree: the media layer of small arteries has small amounts of elastin and elastic lamellae as compared to central vessels, which have higher concentrations of vascular muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors have been identified and, among these, increased arterial stiffness has gained attention due to its correlation with many cardiovascular endpoints [ 1 ]. Studies reported the determinants of arterial stiffness [ 2 ], which contributes to the stiffening of the wall artery. The structure of the vessel wall varies along the vascular tree: the media layer of small arteries has small amounts of elastin and elastic lamellae as compared to central vessels, which have higher concentrations of vascular muscle cells.…”
Section: Introductionmentioning
confidence: 99%